The historical course of the controversy and the location of the controversy from Aristotelian logic - نعمة ابراهيم; مروان أمين (آداب الكوفة, 2015)
This research represents an overview of an aspect of Aristotle (d. 322 BC) the logician, and Aristotle, as is well known to specialists, had great influence in many different fields, but he was more influential in the field of logic than in any other field, and from here he was called the first teacher and the owner of logic . It may seem to some that logic and logical research are rational abstract ideas, and it is at best beneficial to the student in the philosophical matter specifically and has nothing to do with reality and life, but this talk, although it is true, but its implication is not true, because logic is considered one of the closest means by which we know how to think in a nation Certain in a particular era is to see on what logic people proceed in their intellectual processes, because that reveals the way they accept or reject ideas and the way they understand what they understand or do not understand.